FRACTIONATION OF THE N-HEXANE EXTRACT OF GARCINIA BANCANA MIQ. (MANGGIS HUTAN) LEAVES AND ITS ANTIOXIDANT ACTIVITY BASED ON 1,1-DIPHENYL-2- PICRYLHYDRAZYL AND FERRIC REDUCING ANTIOXIDANT POWER ASSAYS - Putri, Dewi Kumala; Elya, Berna; Puspitasari, Nuraini (International Journal of Applied Pharmaceutics, 2018)
Objective: To assess the antioxidant activity from another part of the plant, in this study, leaf extracts in n-hexane were fractionated. Methods: Ten fractions were obtained and tested in vitro for antioxidant activity using two methods, 1,1-diphenyl-2-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP), to identify the most active fraction. Results: The IC50 of the most active fraction was 36.24 Î¼g/mL using the DPPH method, and the EC50 was 39.54 Î¼g/mL using the FRAP method. The most active fraction was also shown to contain terpenoids. Conclusion: The most active fraction of an n-hexane extract of the leaves of Gacinia bancana Miq., which was tested by both DPPH and FRAP methods had antioxidant activities with IC50 and EC50 values of 36.2482 Î¼g/mL and 39.5442 Î¼g/mL, respectively. Phytochemical screening showed that active fraction contains terpenoids.